Transmedia Narrative: a Look at the Armed Conflict and Indigenous Social Memory from Expanded Stories. Cases: Colombia and Peru - Pinto Arboleda, María Cristina (2022)
The main objective of this article is to analyze two Latin American transmedia projects within the framework of non-fiction, circumscribed from the case study method and the application of elements of the Actor-Network Theory, where relationships, the formation of groups social organizations that experienced realities come to develop the value of agency, as an approach that expands and contributes to the understanding and sustainability of the history and experience of the transmedia project over time. The level of impact on the audience of these two narrative systems made it possible to shore up their realities from the articulation of social struggle actions inside and outside the Web. Placing their themes on local and international political and journalistic agendas. Impacts that are retaken in light of the characteristics of non-fiction transmedia formats and their co-creative potentialities, in order to energize social relationships and activate participatory communication within the digital ecosystem.